Growth behavior of interface microstructure between stainless steel and carbon steel during bonding process. (December 2022) - Zhang, Qingdong; Yu, Mingyang; Zhang, Boyang; Li, Hao
Abstract: In this paper, the interface microstructure evolution between stainless steel and carbon steel during the bonding process has been researched. During the bonding process, the interface microstructure of stainless steel/carbon steel composite is always comprised of decarburization carbon steel, intermetallic compound (IMC) layer and carburization stainless steel. The growth behavior of the IMC layer, decarburization carbon steel and carburization stainless steel would obey the parabolic law. The activation energy of the IMC layer, decarburization carbon steel and carburization stainless steel are 60.58 kJ/mol, 100.75 kJ/mol and 76.53 kJ/mol, respectively. The element distribution along the thickness direction would keep unchanged basically in the decarburization carbon steel and carburization stainless steel and would change linearly in the IMC layer. The calculation results of JMatpro have shown that the tensile mechanical parameter of the IMC layer inner area would increase linearly. Graphical Abstract: ga1